Design And Development Of An Autonomous Underwater Vehicle Test-Bed (USM-AUV I). - Arshad, Mohd Rizal; Radzak, Mohamed Yusof (2004)

(untitled)
In this paper, the development of an underwater robotic vehicle is described. The description includes the mechanical and controller design, and the sensor integration.